PRACTICAL TIPS FOR TEACHING VOCABULARY TO YOUNG LEARNERS (Ustozlar uchun, 2025)
This article explores effective and practical methods of teaching vocabulary to young learners. It focuses on how teachers can make vocabulary lessons more engaging, memorable, anad suitable for children’s age and interests. The paper emphasizes the role of creativity, games, visual aids, and storytelling in helping children learn new words naturally and with enjoyment. It also highlights the importance of connecting vocabulary teaching with cultural elements to develop both linguistic and communicative competence.